Correction to: Determinants of healthcare seeking and out-of-pocket expenditures in a “free” healthcare system: evidence from rural Malawi - Nakovics, Meike Irene; Brenner, Stephan; Bongololo, Grace; Chinkhumba, Jobiba; Kalmus, Olivier; Leppert, Gerald; De Allegri, Manuela (Health economics review, 2020)
An amendment to this paper has been published and can be accessed via the original article.
Gesehen am 04.08.2020